T.S. ELIOT'S 'RHAPSODY ON A WINDY NIGHT: A STYLISTIC ANALYSIS - ravinder gargesh (Matn/Pizhūhī-i Adabī, 2004)
The present paper is intended to investigate T.S. ELIOT'S "Rhapsody on a windy night" on the basis of stylistics. The paper contains all three levels of laguage from a stylistics point of view, Attempts will also made to introduce a cohesive form of stylistics within the framework of linguistics